2021
DOI: 10.15584/ejcem.2020.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Low generation polyamidoamine dendrimers (PAMAM) and biotin-PAMAM conjugate – the detailed structural studies by 1H and 13C nuclear magnetic resonance spectroscopy

Abstract: Introduction. The concept of targeted drug delivery is nowadays based on nanoparticle transporters. Such drug delivery systems for cancer cells should follow the requirements like: efficient drug release, selective binding and internalization to cancer cells. The anticancer drug selectivity can be achieved by attachment of cancer cell-recognizing molecules, like biotin. Among nanosized carriers the PAMAM dendrimers are tested intensely, especially they can be modified by covalent attachment of prodrug molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Afterwards, the solvent was removed by vacuum rotary evaporation and dried under high vacuum overnight. The product was identified by 1 H NMR spectroscopy as G3 substituted with average two residues of amide-bonded biotin G3 2B , as described before [ 24 , 25 ]. The isolated yield of the product was 47% (501 mg; 68 μmoles; MW calc = 7362 g mol −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, the solvent was removed by vacuum rotary evaporation and dried under high vacuum overnight. The product was identified by 1 H NMR spectroscopy as G3 substituted with average two residues of amide-bonded biotin G3 2B , as described before [ 24 , 25 ]. The isolated yield of the product was 47% (501 mg; 68 μmoles; MW calc = 7362 g mol −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study we have applied the NMR spectroscopy to characterize the low molecular weight PAMAM G3 conjugates with covalently attached biotin. 25 Later we used PAMAM G3 macromolecular carrier to construct the drug delivery system (DDS) for anticancer drugs: Lapatinib (L) and Fulvestrant (F) and tested those conjugates against three breast cancer cell lines in vitro. 7 We have found that G3-L-F binary conjugate promoted apoptosis in chemotherapy-induced senescent breast cancer cells with different receptor status.…”
Section: G4 Conjugates With Paclitaxel and Fulvestrantmentioning
confidence: 99%